A Fully Validated UHPLC–MS/MS Method for the Estimation of Pimavanserin in Human (K2EDTA) Plasma and its Application to a Clinical Pharmacokinetic Study. (9th June 2021) - Aalapati, Kiran Kumar; Singh, Amit; Patnaik, Ranjana S
Abstract: A simple, fast and extremely sensitive for estimating Pimavanserin in human (K2 EDTA) plasma using ultra high-performance liquid chromatography combined with tandem mass spectrometry (UHPLC–MS/MS) was newly developed and validated. Sample extraction was accomplished using a partition liquid extraction (LLE—liquid–liquid extraction) procedure utilizing extraction solvent, methyl tertiary butyl ether. Separation of the components, chromatography, was done using a C18 chromatographic analytical column employing acetonitrile:methanol: 0.1% formic acid solution (40:40:20 volume by volume) pumped with 0.800 mL/min as the flow rate. For Pimavanserin, the established methodology was linear throughout the calibration curve range from 0.25ng/mL till 50.0 ng/mL. Results of intraday and interday accuracy and precision of Pimavanserin met recent regulatory requirements. This methodology was effectively used to estimate Pimavanserin in vivo human (K2 EDTA) plasma concentration for a clinical pharmacokinetic study.